Aspirin for Primary Prevention of Cardiovascular Events - Abdelaziz, Hesham K.; Saad, Marwan; Pothineni, Naga Venkata K.; Megaly, Michael; Potluri, Rahul; Saleh, Mohammed; Kon, David Lai Chin; Roberts, David H.; Bhatt, Deepak L.; Aronow, Herbert D.; Abbott, J. Dawn; Mehta, Jawahar L. (Journal of the American College of Cardiology, 2019)
The efficacy and safety of aspirin for primary prevention of cardiovascular disease (CVD) remain debatable. The purpose of this study was to examine the clinical outcomes with aspirin for primary prevention of CVD after the recent publication of large trials adding >45,000 individuals to the published data. Randomized controlled trials comparing clinical outcomes with aspirin versus control for primary prevention with follow-up duration of ≥1 year were included. Efficacy outcomes included all-cause death, cardiovascular (CV) death, myocardial infarction (MI), stroke, transient ischemic attack (TIA), and major adverse cardiovascular events. Safety outcomes included major bleeding, intracranial bleeding, fatal bleeding, and major gastrointestinal (GI) bleeding. Random effects DerSimonian-Laird risk ratios (RRs) for outcomes were calculated. A total of 15 randomized controlled trials including 165,502 participants (aspirin n = 83,529, control n = 81,973) were available for analysis. Compared with control, aspirin was associated with similar all-cause death (RR: 0.97; 95% confidence interval [CI]: 0.93 to 1.01), CV death (RR: 0.93; 95% CI: 0.86 to 1.00), and non-CV death (RR: 0.98; 95% CI: 0.92 to 1.05), but a lower risk of nonfatal MI (RR: 0.82; 95% CI: 0.72 to 0.94), TIA (RR: 0.79; 95% CI: 0.71 to 0.89), and ischemic stroke (RR: 0.87; 95% CI: 0.79 to 0.95). Aspirin was associated with a higher risk of major bleeding (RR: 1.5; 95% CI: 1.33 to 1.69), intracranial bleeding (RR: 1.32; 95% CI: 1.12 to 1.55), and major GI bleeding (RR: 1.52; 95% CI: 1.34 to 1.73), with similar rates of fatal bleeding (RR: 1.09; 95% CI: 0.78 to 1.55) compared with the control subjects. Total cancer and cancer-related deaths were similar in both groups within the follow-up period of the study. Aspirin for primary prevention reduces nonfatal ischemic events but significantly increases nonfatal bleeding events. [Display omitted]